Polysaccharide-based nanogels and ocular drug delivery: The emerging nanocarrier for crossing blood retinal barrier - Dharmeshkumar M. Modi; Akshat D. Modi (Carbohydrate Polymer Technologies and Applications, 2023)
The present era demands the development of drug delivery systems that can target therapeutic agents to the site of action with minimal concentration, thereby avoiding unwanted side effects. One of the major obstacles to achieving this objective is the blood-retinal barrier (BRB), which restricts the availability of drugs to the posterior segment of the eye. Traditional methods of drug delivery, such as eye injections and topical application, suffer from low bioavailability and the need for frequent dosing. Nanogels (NGs), a novel drug delivery system, offer a promising solution to this challenge. NGs are comprised of drug particles in the nanometer range and high-viscosity polymer networks, which increases the contact time and facilitates the easy crossing of the BRB. These formulations are easy to prepare, sterilize, and use, and can maintain a desired drug level through initial bursting followed by slow release over time. This narrative review focuses on the growing role of various NGs, including chitosan, chitin, hyaluronan, hyaluronic acid, lysine-carbonized, 2-hydroxypropyl gamma-cyclodextrin, and methylcellulose and poly(N-ter-butylacrylamide) based NGs, in the efficient and safe delivery of drugs to the posterior ocular region by crossing the BRB and avoiding cytotoxicity and immunogenicity.